The Impact of the Epidemic on China's Economy - Wu, Yihan (Transactions on Economics, Business and Management Research, 2024)
This article primarily examines the effects of the epidemic on the civil aviation and catering industries in China. It explores how the pandemic led to a significant downturn in these sectors, contributing to an overall decline in the Chinese economy. The decline was so steep that it resembled a straight line, reflecting the severity of the economic impact. Although the economy is currently on the path to recovery, the repercussions of the epidemic are still being felt across various sectors. At the beginning of the article, a brief comparison is made with the United States to provide a broader context. This comparison highlights how different countries experienced and managed the economic fallout from the pandemic, offering insights into the varying impacts of the crisis globally. The article delves into the multifaceted effects of the epidemic on China, extending beyond just the civil aviation and catering industries. The pandemic altered consumer spending patterns and led to a decline in retail sales. The shift towards online shopping and changes in consumer preferences are discussed, highlighting how businesses had to adapt to new market conditions.